2019
DOI: 10.3390/su11226496
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Household Solid Waste Sorting at Source in Developing Economies: A Case Study of Nur-Sultan City in Kazakhstan

Abstract: The exponential population growth in urban areas makes existing solid waste management policies and strategies challenging. The situation becomes more strenuous in fast-growing cities where increasing waste production can hardly be met by the capacity of existing facilities. Practices like waste prevention, recycling, reuse, and recovery are fundamental elements needed for the reduction of solid waste disposed in landfills, especially in fast-growing cities where more sustainable management practices need to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 54 publications
4
22
0
1
Order By: Relevance
“…Most of the authors involved in SWM studies reported that segregation of waste, which serves as a conduit for the sustainability of SWM, is not well practised or not done in most of the developing countries [11,[42][43][44]. In municipalities where sorting was partially practised, gender and age were the predictive factors of this behaviour, i.e., it was observed that females appeared to be more active in waste separation than males, according to Sarbassov et al [45]. The study of the same authors further indicated that two-thirds of sorted waste in the developing countries is done by the elderly (50 years and above), and no separation or a small amount is done by the age range of 5-17 years, while almost one-third of the segregated waste is done by people within the ages of 18-39.…”
Section: Literature Review 21 Solid Waste Management-courses and Effects Of Poor Management Of Swm In Developing Countriesmentioning
confidence: 99%
“…Most of the authors involved in SWM studies reported that segregation of waste, which serves as a conduit for the sustainability of SWM, is not well practised or not done in most of the developing countries [11,[42][43][44]. In municipalities where sorting was partially practised, gender and age were the predictive factors of this behaviour, i.e., it was observed that females appeared to be more active in waste separation than males, according to Sarbassov et al [45]. The study of the same authors further indicated that two-thirds of sorted waste in the developing countries is done by the elderly (50 years and above), and no separation or a small amount is done by the age range of 5-17 years, while almost one-third of the segregated waste is done by people within the ages of 18-39.…”
Section: Literature Review 21 Solid Waste Management-courses and Effects Of Poor Management Of Swm In Developing Countriesmentioning
confidence: 99%
“…Considering local state, in Kazakhstan, roughly 4.3 million tons of MSW was produced in 2018, and this quantity is expected to increase to 7 M tons by 2030 [2,3]. Even though some elements of the waste management practices have been implemented in Kazakhstan, including source separation of recyclables (plastics and cardboards) and battery and electronic waste containers, the disposal of MSW in sanitary landfills is still dominates in major cities [4]. The current capital city of Kazakhstan, Nur-Sultan city (previously named as Astana city) has been growing continuously since the capital city was transferred from Almaty city in 1998 [5].…”
Section: Introductionmentioning
confidence: 99%
“…We used a 5-point Likert type scales (1 = Strongly Disagree, 5 = Strongly Agree) and 3-point type scale (Yes, No, Not Sure). The choice of 5-point Likert scale is based on the fact that the survey is presupposed for municipality residents, and this system is more acceptable for the elderly persons who understand the school time 5-point grading system [50,51].…”
Section: Methodsmentioning
confidence: 99%